1987
DOI: 10.1590/s0034-89101987000600003
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e estado nutricional de crianças de 0-11 anos, Estado da Paraíba (nordeste brasileiro)

Abstract: CARIRI BENIGNA, M. J. Crescimento e estado nutricional de crianças de 0-11 anos, Estado da Paraíba (nordeste brasileiro). Rev. Saúde públ., S. Paulo, 21:480-9, 1987. RESUMO:Compara-se o crescimento do peso-idade e da altura-idade de 7.990 crianças de 0-11 anos, aleatoriamente selecionadas e medidas em 1981-1982 no Estado da Paraíba (nordeste do Brasil), com o de estudo global realizado no nordeste em [1974][1975], com as curvas de crescimento das referências nacional e internacional. Os resultados colocam em e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
2
1
1
Order By: Relevance
“…Our study confirms the prevalence of dental fluorosis and malnutrition previously reported [Sampaio, 1993;Benigna et al, 1987;Victora et al, 1991;PESN, 1992;Sampaio et al, 1997], and suggests that malnutrition and dental fluorosis are independent phenomena in this area.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirms the prevalence of dental fluorosis and malnutrition previously reported [Sampaio, 1993;Benigna et al, 1987;Victora et al, 1991;PESN, 1992;Sampaio et al, 1997], and suggests that malnutrition and dental fluorosis are independent phenomena in this area.…”
Section: Discussionsupporting
confidence: 92%
“…Our data show the mean height of boys to be 5-10 cm higher than reported in the last survey in Paraíba [Benigna et al, 1987] (fig. 2).…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…Among low-income populations, short stature is very often attributed to living conditions and chronic malnutrition. The effect of environment on growth is well established (31)(32)(33)(34) . It is known that unhealthy living conditions and chronic malnutrition are negative stimuli and that the malnutrition caused by poverty is most obviously manifest in failure to thrive (32,33) .…”
Section: Referencesmentioning
confidence: 99%
“…12,20,33,[73][74][75][76][77][78] Na Paraíba, Benígna et al 73 Anjos, 1 investigando o estado nutricional de 185 crianças em idade escolar (7,0 a 10,9 anos) de baixa renda familiar, freqüentadoras de uma escola da rede pública do município de Nova Iguaçu, Estado do Rio de Janeiro, observou que a desnutrição recente (índice peso/idade) era de 3,52%, enquanto a desnutrição crônica (nanismo nutricional) alcançou 6,25% (z <-2).…”
Section: Magnitude Do Nanismo (Déficit Estatural)unclassified